VD_FINDINFO Pron / 2011 / 3 vom 16. Dezember 2010 - VD Tribunal cantonal (2010)
JUGE ARBITRE, EXPERT-ARBITRE | 2 C-Arb, 3 C-Arb, 45 al. 1 C-Arb, 425 CPC, 426 CPC, 92 al. 1 CPC, 10 al. 1 LFors, 22 LFors